2012
DOI: 10.1083/jcb.201201100
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic cohesin complexes are essential for the formation of the axial element in mice

Abstract: Loss of both meiosis-specific kleisins in mice reveals conserved functions of the meiotic cohesin complexes in axial element formation during spermatogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
155
2
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(176 citation statements)
references
References 60 publications
12
155
2
3
Order By: Relevance
“…Although SC assembly occurs solely between sisters in Rec8 knockout spermatocytes as reported (Bannister et al 2004;Xu et al 2005), Rad21L knockout spermatocytes assemble SC at both intersisters and interchromosomes ( Fig. 4B; Llano et al 2012). In contrast to the results using mice with a single mutation, Rec8/Rad21L doubleknockout mice (male and female) did not form either cohesin axes or chromosome axes, including SYCP3 ( Fig.…”
Section: Cohesin and Chromosome Architecturecontrasting
confidence: 50%
See 2 more Smart Citations
“…Although SC assembly occurs solely between sisters in Rec8 knockout spermatocytes as reported (Bannister et al 2004;Xu et al 2005), Rad21L knockout spermatocytes assemble SC at both intersisters and interchromosomes ( Fig. 4B; Llano et al 2012). In contrast to the results using mice with a single mutation, Rec8/Rad21L doubleknockout mice (male and female) did not form either cohesin axes or chromosome axes, including SYCP3 ( Fig.…”
Section: Cohesin and Chromosome Architecturecontrasting
confidence: 50%
“…3J,K), suggesting that RAD21L and REC8 redundantly function in forming the cohesin axis, a base for the assembly of the AE (Fig. 7, below ;Llano et al 2012). Immunogold electron microscopic analyses revealed that cohesin complexes localize on the innermost sides of the two lateral elements in wild-type bivalents (Fig.…”
Section: Cohesin and Chromosome Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that, in this case, the cohesin core is sufficient to allow the binding of the TFs (Pelttari et al 2001). Disruption of the AEs and major parts of the cohesin core, as it is found in the kleisin double mutant Rec8 -/-Rad21l -/-, however, finally leads to a failure in SYCP1 association as well (Llano et al 2012). In the wild-type situation, SYCE3 is recruited to SYCP1 in the next step followed by SYCE1.…”
Section: Second Step: the Assembly Of The Central Regionmentioning
confidence: 99%
“…SMC1ß (Revenkova et al 2004) or REC8 (Bannister et al 2004), affects AE morphology and assembly. It even completely abolishes the AE formation if the two meiotic kleisin subunits REC8 and RAD21L are depleted in a double knock-out (Llano et al 2012). This suggests that the cohesion core is necessary for the assembly of a defined AE.…”
Section: First Step: the Assembly Of The Chromosomal Axes And The Aximentioning
confidence: 99%